Relation between sociability, blood pressure and heart rate in the domestic dog (Canis familiaris) - Cainzos, Romina (2018)
The aim of the study was to evaluate heart rate (HR) and blood pressure (BP) in domestic dogs of a breeding facility in the city of Corrientes, Argentina in response to contact with an unknown person, taking into account whether sociability influences these responses. A total of 18 adult dogs, aged 1 to 8 years, of both sexes, of the Smooth Fox Terrier, Wire Hair Fox Terrier and Beagle breeds were studied. A sociability test was applied, consisting of two phases of two minutes each. In the passive phase the person does not interact with the animal and in the active phase the person interacts with the animal through caresses. The variables of latency, physical and visual contact and signs of fear/submission were registered. Based on the responses, the animals were distributed in a less social group (1, n=9) and a more social group (2, n=9). Blood pressure (systolic [PS], diastolic [PD], mean [PM]) and heart rate (FC) were determined before and after interaction with the unknown person. Dogs of group 2 (sociable) showed significant differences in PS and FC measurements before and after the interaction (p=0.02 and p=0.04, respectively). Likewise, there was a significant difference between groups for the PS variable after interaction with the person (p=0.03). The interaction with the unknown person increased the FC and PS in the less social dogs, while the PS decreased in social dogs.